Comparison of Behavioral Disorders, Compromise Behaviors and Academic Achievement of Exceptional Students in Especial Educational System and Integrated Educational System - Davoud Fathi; Farnaz Keshavarzi-Arshadi; Mahmoud Jamali-Firouzabadi; Omid Massah-Choulaby (University of Social Welfare and Rehabilitation Sciences, 2011)
Objective:The purpose of this study is to compare the educational progress and behavioral compromise of exceptional students in special educational system and integrated system in Hamedan province. Materials & Methods:This research is based on comparison between all the exceptional students who divided in two groups of blind and deaf in three levels in clouding primary, guidance and high school students. 40 students from integrated and 40 students from especial educational system with cluster sampling method were selected the rate of P is considered as q .The rate of p was considered equal 0.5 and the rate of q equal 0.5 . Then for gathering data a questionnaire based on Akhnbakh experience was used . The data were analysed in &alpha= 0.05 level with independent T test and multivariate analysis of MANOVA variance . Results: The result showed that there is a significant difference between the amount of educational progress , compromise behaviors , amount and kind of abnormal behaviors of exceptional students in integrated educational system with special educational system . Also the rate of educational progress and compromise behaviors is better in integrated system than especial educational system . Moreover disordered behaviors of these students are less than their counterparts in special educational system . Conclusion: in general integrated educational system in comparison with especial educational system is most successful in field of educational progress ,compromise behavior and abnormal behavior in exceptional students (blind and deaf).